Impact of the COVID-19 pandemic on the antimicrobial resistance at the General Hospital level in Republic of Srpska, Bosnia and Herzegovina - Nasta Manojlović; Biljana Mijović; Zlatko Maksimović; Dragana Sokolović; Sanda Lazić; Ljubica Bojanić; Dragana Drakul; Nenad Lalović; Marija Lukić; Bojan Joksimović (Биомедицинска истраживања, 2024)
Introduction: Antibiotic resistance is a major threat to public health globally. The aim was to examine the impact of the COVID-19 pandemic on the distribution and antimicrobial resistance of pathogenic microorganisms isolated from samples obtained during standard hospital care in one hospital center. Methods: Data were obtained retrospectively from a database of the hospital microbiology laboratory. Study sample consisted of 3012 samples tested before the pandemic in 2019 and 3130 samples from the pandemic period in 2021. Results: There was no statistically significant difference in the occurrence of agents that were resistant to all antibiotics between the observed years, but there was the difference in the occurrence of those agents between departments, with the highest frequency in the intensive care unit and the COVID-19 department (p<0.001). Isolation of Acinetobacter bacteria increased 2.7 times, and Clostridioides difficile 6.4 times during 2021 compared to 2019. Statistically significant differences were registered in resistance to: imipenem, piperacillin-tazobactam, ceftayidime, cefepime, glycopeptides, aminoglycosides, levofloxacin and ciprofloxacin in 2021 compared to 2019. Conclusion: Our results suggest possible influence of COVID-19 on antimicrobial resistance and input a need for a new larger study addressing this issue.
Keywords: Antimicrobial resistance; COVID-19; multiresistant bacteria